In vitro activity of two cycloartane-type triterpenoid saponins from Astragalus glycyphyllos on liver microsomes, hepatocytes, and isoforms of cytochrome P450 - Ivan Stambolov; Magdalena Kondeva-Burdina; Aleksandar Shkondrov; Ilina Krasteva (Pharmacia)
Two cycloartane-type saponins 3-O-[α-L-rhamnopyranosyl-(1→2)]-β-D-xylopyranosyl]-24-O-α-L-arabinopyranosyl-3β,6α,16β,24(R),25-pentahydroxycycloartane and Astrachrysoside A, obtained from the aerial parts of A. glycyphyllos, were tested in vitro for their possible hepatoprotective and antioxidant effects. Three models were used: isolated liver microsomes (non-enzyme-induced lipid peroxidation) and hepatocytes (t-BuOOH-induced oxidative stress and CCl4-induced metabolic bioactivation). Both compounds (50 µM) exhibited statistically significant activity in all of the models, compared to the control. The saponins` hepatoprotective activity was even more pronounced in the metabolic bioactivation model. In addition, the compounds (1 µM) were evaluated for possible inhibitory activity on three isoforms of cytochrome P450. Both saponins exhibited noticeable inhibition on CYP3A4, mild inhibition oF CYP2D6, and no activity on the CYP1A2 isoform was observed.